2017
DOI: 10.1149/07542.0003ecst
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Solid Oxide Electrolysis Improvements at DTU Energy

Abstract: Solid oxide electrolysis cells (SOECs) can efficiently convert electrical energy (e.g. surplus wind power) to energy stored in fuels such as hydrogen or other synthetic fuels. Performance and durability of the SOEC has increased orders of magnitudes within the last decade. This paper presents a short review of the R&D work on SOEC single cells conducted at DTU Energy from 2005 to 2015. The SOEC improvements have involved increasing the of the oxygen electrode performance, elimination of impurities in the feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…Such a device is usually operated in the relatively high‐temperature range of 700 to 900 °C, thus resulting in a high conversion efficiency, because (a) a significant part of the required energy can be provided by external heat for an ideal HTE and (b) the electrode reaction kinetics are faster at higher temperatures . To date, extensive efforts have been devoted to the development of highly efficient SOECs and promising results have been obtained …”
Section: Introductionmentioning
confidence: 99%
“…Such a device is usually operated in the relatively high‐temperature range of 700 to 900 °C, thus resulting in a high conversion efficiency, because (a) a significant part of the required energy can be provided by external heat for an ideal HTE and (b) the electrode reaction kinetics are faster at higher temperatures . To date, extensive efforts have been devoted to the development of highly efficient SOECs and promising results have been obtained …”
Section: Introductionmentioning
confidence: 99%
“…a multilayer tape casting (MTC) process and lamination process was applied [14]. These four MTC layers of the tapes were cut into 16x16 cm 2 pieces and co-sintered at 1315 C [18] and then cut into 53x53 mm 2 cells. The oxygen electrode (40x40 mm 2 ) was applied by screen-printing and sintered at 930 C.…”
Section: Cell Specifications and Test Set-upmentioning
confidence: 99%
“…The justification of including this contribution upon CNLS fitting of the experimental IS is based on previous work e.g. with SOC having different support layer microstructures [18]. Figure 6 shows the fuel electrode/electrolyte interface for Cell A and Cell C after electrolysis testing for 1000 h and 2000 h, respectively.…”
Section: Initial Microstructuresmentioning
confidence: 99%
“…Because the Ni-based cathode exhibits porous structure, high electronic conductivity, appropriate catalytic activity and close thermal expansion coefficient (TEC) with the electrolyte, it could act as an excellent SOECs cathode for CO 2 /H 2 O co-electrolysis, and thus has drawn intense corresponding studies [37,[47][48][49][50] . Mogensen and co-workers have evaluated the performance, reaction mechanism and the durability of Ni-cermets cathodes for CO 2 /H 2 O co-electrolysis in single SOEC or SOEC stacks for decades [7,15,24,25,29,30,48,51,52] . It has been demonstrated that the Ni-cermets cathodes indeed display a high catalytic activity for CO 2 /H 2 O co-electrolysis.…”
Section: Ni-cermet Cathodementioning
confidence: 99%